Improving the generalization ability of neuro-fuzzy systems by [epsilon]-insensitive learning - Łęski, Jacek M. (Zielona Góra: Uniwersytet Zielonogórski)
A new learning method tolerant of imprecision is introduced and used in neuro-fuzzy modelling. The proposed method makes it possible to dispose of an intrinsic inconsistency of neuro-fuzzy modelling, where zero-tolerance learning is used to obtain a fuzzy model tolerant of imprecision.
Keywords: fuzzy systems; neural networks; tolerant learning; generalization control; robust methods